Efektivitas Edukasi Berbasis Video terhadap Perubahan Pola Makan Sebagai Upaya Pencegahan Obesitas pada Remaja - Winda Agustina; Hasanah Pratiwi Harahap; Marlina; Yuka Oktafirnanda (Universitas Islam Jember, 2026)
More than 390 million adolescents worldwide were reported to be obese. Unhealthy eating patterns are the main contributing factors. prevention is therefore essential, one of which can be achieved through engaging and easily understandable educational approaches such as health promotion using video media. This study aimed to determine the effectiveness of video-based education on dietary habits for the prevention of obesity. Methods: This research employed a true experimental design with a pretest-posttest control group approach. The study population consisted of 233 tenth-grade students, with a sample of 70 respondents selected using proportionate stratified random sampling. Data analysis was conducted using the Paired Sample T-Test. Result: The results indicated a significant difference in dietary habits before and after the video intervention (p < 0.05), these findings suggest that video-based education effectively improved dietary habits. Educational interventions through video media can serve as an effective promotion method, as they can deliver health messages in an engaging and efficient manner. It is hoped that the results of this study can encourage teenagers to be more active in maintaining their diet to avoid obesity.